Authoritative governance policy-making in the age of mediatization - Hajer, Maarten A., 1962- (Oxford : Oxford University Press, 2009)
Here, one of the world's leading analysts of public policy offers a radical new interpretation of governance and authority in a media-driven age. Three case studies are featured to help bring the argument to life.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communication in public administration; Political planning; Mass media -- Political aspects; Legitimacy of governments; Government publicity -- Public opinion; Public administration -- Press coverage